The Exercise of Moral Rights by Non-Authors - Aleksei Kelli; Thomas Hoffmann; Heiki Pisuke; Irene Kull; Liina Jents; Carri Ginter (Law: Journal of the University of Latvia, 2022)
The concept of moral rights is as old as authors’ rights (droit d’auteur) themselves. It was intended to protect the author’s honour and reputation. The rights of attribution, integrity and disclosure constitute the core of the author’s moral rights. During the 20th century, moral rights became a universal category of copyright law.